2021
DOI: 10.21203/rs.3.rs-231323/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimization of random forest model for assessing and predicting geological hazards susceptibility in Lingyun County

Abstract: The frequent occurrence of geological hazards will not only cause peoples' property loss and deterioration of living environments, but will also endanger peoples' lives. Therefore, rapid and accurate evaluation of geological hazards susceptibility can provide an important scientific basis for emergency rescue and disaster reduction and prevention. In this paper, ten effective variables including slope, aspect, curvature, normalized differential vegetation index, annual precipitation, strata lithology, tectonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Also, at high elevations, strong ground motion is ampli ed by the slope crest much more than at the slope toe(Qi et al 2003(Qi et al , 2006Sepúlveda et al 2005; Yao et al 2021;Zou et al 2022). The simple structure of the ANN model can help to fully understand the complex linear relationship or nonlinear relations between landslides and controlling parameters(Kong et al 2021). This study showed that the separation of landslides triggered by earthquakes into different types can be used to better predict the LA, as well as to understand failure mechanisms based on the controlling parameters.…”
mentioning
confidence: 99%
“…Also, at high elevations, strong ground motion is ampli ed by the slope crest much more than at the slope toe(Qi et al 2003(Qi et al , 2006Sepúlveda et al 2005; Yao et al 2021;Zou et al 2022). The simple structure of the ANN model can help to fully understand the complex linear relationship or nonlinear relations between landslides and controlling parameters(Kong et al 2021). This study showed that the separation of landslides triggered by earthquakes into different types can be used to better predict the LA, as well as to understand failure mechanisms based on the controlling parameters.…”
mentioning
confidence: 99%